The psychological trauma causing isolation in Jeevan Jeevant's Charaiveti (Journal of Population and Development, 2024)
The novel Charaiveti of Jeevan Jeevant is a Nepali flavoured writing which has the novelist's suffering after his father's refusal of keeping altar in own house amidst his two daughters' death; the forceful conversion of author's father into Christianity in the sense that he wants to regret of his past misdeed to his altar but the neighbours blame him continuously to have already left the Sanatan-Hindu religion; the consequent and unwilling migration from mountainous parental home to the Madhesh after the family clash; the police torture for adopting Christianity, and so on. This article broadly seeks the objectives that whether there are series of miseries and tortures after the works of religious conversion and migration from one place to another in the life of a person. To obtain the objectives, the writer of this article uses the qualitative method in which the Lacanian theory of trauma of the Real operates the matter. The researcher consults various texts including the novel, theoretical texts and some commentaries on the novel to reach the facts of the mental frame of the novelist's father of an islandish existence even in the society as central character. This study results a positive understanding of the life of any type of minority either religion or caste and region at new place. Such positive learning of life of a migrant and forceful religiously converted ownself will become a good moral lesson for the society to respect the individual's notions for social harmony and even to conservation of own religion and culture.